Loss of heterozygosity in lobular carcinoma in situ of the breast. Issue 2 (April 1995) - Lakhani, S R; Collins, N; Sloane, J P; Stratton, M R
Abstract : Aims —(1) To investigate whether loss of heterozygosity identified at various loci in invasive breast carcinoma or is present in lobular carcinoma in situ (LCIS). (2) To investigate whether LCIS is a monoclonal (neoplastic) or a polyclonal (hyperplastic) proliferation. Methods —Forty three cases of LCIS (30 with associated invasive carcinoma or in situ ductal carcinoma (DCIS) and 13 cases of pure LCIS) were investigated for loss of heterozygosity on chromosomes 16q, 17q, 17p, and 13q using a microdissection technique, polymorphic DNA markers, and the polymerase chain reaction (PCR). Results —Loss of heterozygosity was detected in both subgroups of LCIS at all the loci examined. There was no significant difference in the frequency of the loss between the group associated with invasive carcinoma and the pure LCIS group. The frequency of loss of heterozygosity ranged from 8% on 17p to 50% on 17q. Conclusions —Because of the nature of the technique employed, our findings show that LCIS is a monoclonal (neoplastic) proliferation rather than a hyperplastic proliferation. The incidence of loss of heterozygosity on 17p (D17S796) is lower than we have observed previously in DCIS, suggesting that LCIS and DCIS are different genetically as well as clinically and morphologically. The similar incidence of loss of heterozygosity on 16q and 17q, however, suggests that DCIS and LCIS may share a common pathway of evolution.